PENERAPAN CARA BUDIDAYA IKAN YANG BAIK PADA PEMBESARAN UDANG VANAME (Litopenaeus vannamei) DI PESISIR DAERAH ISTIMEWA YOGYAKARTA - Lucky Restyan Nugroho; Sukardi Sukardi; Bambang Triyatmo (Universitas Gadjah Mada, 2016)
This study aims to apply a good fish farming methods and determine factors that influence development the vaname shrimp (Litopenaeus vannamei) in the coast of Yogyakarta Special Region. This research also aims to find out an applicable technology of shrimp aquaculture for fish farmers in the coastal area of Special Region of Yogyakarta. The basic method used in this research is descriptive research with research instrument in the form of a questionnaire. The descriptive research aims to provide a picture of a society, a particular group of people or a picture of a symptom. Data collection techniques are conducted by interviews and structured observation to obtain a more detailed picture of a phenomenon. The location of the research is determined by purposive sampling, focusing on Sidorejo, Banaran, Galur, Kulon Progo, Kuwaru and Ngentak, Poncosari, Srandakan, Bantul. The reason for taking 3 areas is because as the center of production of shrimp vaname first and the longest operates in the coastal area ofSpecial Region of Yogyakarta. Respondents were determined by proportionate random sampling from 3 specified areas. This research took place from June 18, 2015, to July 12, 2015. The results showed the application of the good fish farming method on the activity of enlargement of shrimp vaname (L. vannamei) on the coast of Special Region of Yogyakarta covers 10 parameters. These ten parameters include site selection; determination of construction layout and design; selection of cultivation containers; biosecurity; selection of fish seed (shrimp); use of fish feed (shrimp); use of probiotics; use of disinfectants; harvesting method and harvesting equipment. Application of good fish farming method at vaname shrimp (L. vannamei) aquaculture development in the coast of Yogyakarta Special Region averaged at 62.24%. Factors that influence the application of good fish farming in the shrimp aquaculture development activities are the existence of communication and socialization services on the technical methods for the shrimp aquaculture by employees of feed and probiotics companies. Counseling (communication and socialization), verification (recording) and control in the form of certification has not been done by the Department of Marine and Fisheries of Indonesia. The technology of vaname shrimp farming (L. vannamei) applied by farmers in the coast of Yogyakarta Special Region is semi-intensive technology.